The theory of splines and their applications - Ahlberg, J. H. (J. Harold); Nilson, Edwin N. (Edwin Norman); Walsh, J. L. (Joseph Leonard), 1895-1973 (Mathematics in science and engineering, 1967)
Spline functions constitute a relatively new subject in analysis. During the past decade both the theory of splines and experience with their use in numerical analysis have undergone a considerable degree of development. This book makes some serious effort to organize and present material developed up to this time. This book contains much material published since 1956, together with a considerable amount of the authors' own research, and reflects the authors considerable amount of practical experience with splines.